2022
DOI: 10.1093/infdis/jiac057
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of an Anti-Ebola Serology for the Management of Clinically Suspected Ebola Virus Disease Patients Discharged as Negative in an Epidemic Context

Abstract: Survivors from Ebola virus disease (EVD) may be at the origin of EVD resurgence. Simultaneous reactivity to at least two EBOV antigens was detected in 11/488 (2.3%, 95% CI 1.1-4.0) suspected EVD patients discharged as negative after two consecutive negative tests during the tenth Ebola outbreak in the DRC. Extrapolating on the total number of individuals discharged as negative during the entire outbreak, suggests a total of 1,314 additional missed Ebola cases. These findings emphasize the usefulness of an EBOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, this integrated view is still likely to be incomplete, as some cases and contacts could only be identified as probable, suggesting that additional EVD cases might not have been fully documented, which was similar to observations from the tenth EVD outbreak in Nord Kivu Province, Democratic Republic of the Congo. 21 In our epidemiological case investigations, we reported evidence that the 2020 Équateur Province EBOV outbreak started in the Mbandaka health zone and originated from an individual who frequently consumed bat meat and, using genetic data, we demonstrated that the EBOV sequence from the index case represented a new Ebola virus variant. Using additional genetic evidence, we demonstrated that a second EBOV variant re-emerged from an EVD survivor of the previous 2018 Équateur outbreak during the same timeframe.…”
Section: Discussionmentioning
confidence: 78%
“…However, this integrated view is still likely to be incomplete, as some cases and contacts could only be identified as probable, suggesting that additional EVD cases might not have been fully documented, which was similar to observations from the tenth EVD outbreak in Nord Kivu Province, Democratic Republic of the Congo. 21 In our epidemiological case investigations, we reported evidence that the 2020 Équateur Province EBOV outbreak started in the Mbandaka health zone and originated from an individual who frequently consumed bat meat and, using genetic data, we demonstrated that the EBOV sequence from the index case represented a new Ebola virus variant. Using additional genetic evidence, we demonstrated that a second EBOV variant re-emerged from an EVD survivor of the previous 2018 Équateur outbreak during the same timeframe.…”
Section: Discussionmentioning
confidence: 78%
“…Seropositivity was very high when looking at serology in people who had past infections e.g. (36) compared to the general population e.g. (37).…”
Section: Discussionmentioning
confidence: 99%
“…While the EBOV seroprevalence in Boende after the previous epidemic of 2014 was high (28.1%) among healthy HCP never reporting an infection [24], the seroprevalence estimate was much lower in another study conducted in the same area (7%) [22]. A serosurvey conducted on blood samples collected from clinically suspected EVD cases that were sent home after testing negative in two consecutive EBOV RT-PCR during the tenth EBOV outbreak in DRC Ituri, Nord Kivu and Sud Kivu provinces, 2018-2020), reported an EBOV antigen seroreactivity of 2.3% [25] (Table 1). However, despite many studies assessing the GP-EBOV antigen seroreactivity in different populations and different locations/countries, the interpretation of this seroprevalence data is challenging given the variation of the assays employed and diversity of cutoff algorithms used [8,12,18,[26][27][28].…”
Section: Introductionmentioning
confidence: 89%